2016
DOI: 10.1515/geo-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

FLIRE DSS: A web tool for the management of floods and wildfires in urban and periurban areas

Abstract: A web-based Decision Support System, named FLIRE DSS, for combined forest fire control and planning as well as flood risk management, has been developed and is presented in this paper. State of the art tools and models have been used in order to enable Civil Protection agencies and local stakeholders to take advantage of the web based DSS without the need of local installation of complex software and their maintenance. Civil protection agencies can predict the behavior of a fire event using real time data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In their paper, Kochilakis et al [6] present FLIRE DSS, a web-based decision support system for forest fire control and planning and flood risk management for real-time use in natural disaster management. The system can be used by government agencies to predict fire and flooding events using real-time data, in order to stop fires from spreading and to draft evacuation plans.…”
Section: Papers Presentedmentioning
confidence: 99%
“…In their paper, Kochilakis et al [6] present FLIRE DSS, a web-based decision support system for forest fire control and planning and flood risk management for real-time use in natural disaster management. The system can be used by government agencies to predict fire and flooding events using real-time data, in order to stop fires from spreading and to draft evacuation plans.…”
Section: Papers Presentedmentioning
confidence: 99%
“…In addition to the above two approaches, some scholars have established different DSS based on other methods, but their research purposes are also to solve or simulate similar risk issues such as evacuation in specific fire scenarios. Kochilkis et al established a web-based DSS that primarily implements fire control and planning for forests and risk management of floods [10]. Pribyl et al established a new practical road tunnel risk analysis system that reduces the cost of the tunnel safety system [11].…”
Section: Introductionmentioning
confidence: 99%
“…BA[77,86,90,149,172,[180][181][182][183][184][185][186][187][188][189] Big Data[29,45,145,181,[190][191][192][193][194][195] Figure6. Number of studies found versus the problem to be solved.…”
mentioning
confidence: 99%